2018
DOI: 10.1093/ehjci/jey146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between patient presentation and morphology of coronary atherosclerosis by quantitative multidetector computed tomography

Abstract: Aims Quantitative computed tomography (QCT) allows assessment of morphological features of coronary atherosclerosis. We aimed to test the hypothesis that clinical patient presentation is associated with distinct morphological features of coronary atherosclerosis. Methods and results A total of 1652 participants, representing a spectrum of clinical risk profiles [787 asymptomatic individuals from the general population, 468 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This finding is most likely due to differences in plaque composition and disease burden between the investigated subpopulations. It has been shown that coronary atherosclerotic plaque volume and composition are strongly associated to clinical presentation and several studies have previously reported increased total non-calcified plaque volume and low attenuation plaque volume in patients with ACS compared to patients with stabile angina and asymptomatic individuals [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is most likely due to differences in plaque composition and disease burden between the investigated subpopulations. It has been shown that coronary atherosclerotic plaque volume and composition are strongly associated to clinical presentation and several studies have previously reported increased total non-calcified plaque volume and low attenuation plaque volume in patients with ACS compared to patients with stabile angina and asymptomatic individuals [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
“…27 Patients with acute chest pain diagnosed with ACS had increased atherosclerotic plaque volume, notably fibro-fatty and necrotic core plaque, when compared to those with stable disease. 92 The ICONIC (Incident COroNary Syndromes Identified by Computed Tomography) casecontrol series is the largest (n=234 matched case and control pairs) to evaluate quantitative CCTA precursors of ACS. In ICONIC, both HRP features and quantitative assessment of fibrofatty and necrotic core plaque volume was more often associated with patient experiencing ACS; independent of coronary stenosis.…”
Section: Quantitative Plaque Assessment and Prognostic Value For Majomentioning
confidence: 99%
“… 66 In fact, compared with asymptomatic patients, those with acute chest pain have a greater volume of total and low-attenuation plaque, particularly those with non-ST-segment elevation myocardial infarction. 67 In the RAPID-CTCA trial, the burden of total, noncalcified, and low-attenuation plaque were the strongest predictors of death or myocardial infarction at one year, independent of GRACE score and the presence of diameter stenosis ≥70%, among patients with suspected acute coronary syndrome. 68 Furthermore, CTCA along with quantitative plaque analysis potentially helps discriminate acute coronary syndrome by characterising adverse plaque features.…”
Section: Future Directionsmentioning
confidence: 94%